Survey for hymenopteran parasitoids from forest stand and rice field area - Idham Cholik Ramadhan; Manap Trianto; Dirham Dirham (Jurnal Biologi Tropis, 2022)
Hymenopteran order is an order of insects that is useful for pollinating plants, producing honey and wax and can kill insects that harm plants (pests). This study aims to determine the results of collections of Hymenoptera parasitoid insects from forest stands and rice fields. The research was carried out in January-March 2019. The sampling locations were carried out in two types of areas, namely forest stands and rice fields. Based on the results of the study, it was found that the two orders of insects that had a dominant number from the collection were the Order Diptera and Order Hymenoptera. The number of Hymenoptera insects in the forest stands and rice fields were 1.586 individuals and 2.179 individuals, respectively, with a total of 21 families of parasitoid insects. The use of separators in the collection of Hymenoptera parasitoid insects has several advantages compared to using other insect net, namely making it easier to collect insects and the number of insects caught is also higher.